Socio-economic supports available for the education of adolescent girls in child-headed families in the Kingdom of Eswatini: Policy Implication for Educational Evaluators - K.Thwala, S’lungile; S. Ugwuanyi, Christian; I.O. Okeke, Chinedu; Ncamsile, Ngwenya (International Journal of Psychosocial Rehabilitation, 2021)
The study sought the socio-economic supports available for the high school adolescent girl learners from child-headed families (CHFs). The study used the phenomenological research design using a total of 40 learners from five (5) rural schools, who were randomly selected for the study. Data were collected using focus group discussions and individual interviews. Data collected were thematically analyzed by scrutinizing them for commonalities. The findings of the study revealed that the adolescent girls in CHFs receive the majority of their socio-economic supports from the communities and non-governmental organizations, while the government does not do much for them in terms of their socio-economic needs for their education. Hence, the participants expected from government full support for them in terms of their educational and socioeconomic needs.These findings have policy implications for educational evaluators across the globe. This implies that educational evaluators, in conjunction with the appropriate government authority, need to come up with a workable policy document to submit the children from CHFs. It was recommended that the Ministry of education and Training make frantic efforts to ensure that the educational needs of adolescent girls in CHFs are met